2020
DOI: 10.1080/23311843.2020.1868171
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of different prescribed fire frequencies on selected soil chemical properties in a semi-arid savannah thornveld

Abstract: Citation informationCite this article as: Impacts of different prescribed fire frequencies on selected soil chemical properties in a semi-arid savannah thornveld, C.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…Additionally, we recommend additional studies on the frequency of low-severity burns, as most in the study area are annual. These studies will be essential to discern their impacts, considering that repeated annual burns, including low-severity ones, may reduce soil carbon compared to less frequent burns (biannual, triennial, and quadrennial) [ 92 ]. However, we advocate for the integration of traditional knowledge to enhance our understanding of the benefits of low-severity fire on human well-being [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, we recommend additional studies on the frequency of low-severity burns, as most in the study area are annual. These studies will be essential to discern their impacts, considering that repeated annual burns, including low-severity ones, may reduce soil carbon compared to less frequent burns (biannual, triennial, and quadrennial) [ 92 ]. However, we advocate for the integration of traditional knowledge to enhance our understanding of the benefits of low-severity fire on human well-being [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, we propose the need to implement alternatives in the studied areas to reduce the annual use of fire, avoiding possible negative impacts, as indicated by recent studies [ 92 ]. Among the main strategies and alternatives to the use of fire are the adoption of conservation agricultural practices, the implementation of agroforestry and silvopastoral systems, productive diversification and the production of organic fertilizers using crop residues and productive processes, such as those developed in some areas of Ecuador [ 93 ].…”
Section: Discussionmentioning
confidence: 99%
“…Due to their size, the large field plots such as the current trial are difficult to replicate. Several articles have since been published using the improved sampling design and strategy (Materechera et al, 1998;Magomani and van Tol, 2019;Parwada et al, 2020) and this indicates the reproducibility of the experiment. The current trial sampling was completed prior to the initiation of the 42nd year of treatments in the experiment.…”
Section: Site Description Experimental Design and Samplingmentioning
confidence: 96%
“…The main rainy season commences around October and ends around March, with 70% of rainfall being distributed across this period [18]. The vegetation type of the study area is Bisho thornveld, found in a semi-arid savanna biome, with Vachelia karoo dominating a mixed woody landscape [20]. The herbaceous vegetation is dominated by the following C4 perennial bunchgrasses: Themeda triandra, Digitaria eriantha, Sporobolus fimbriatus, Cymbopogon plurinodis, and Eragrostis species.…”
Section: Study Areamentioning
confidence: 99%